Delegating budgets when agents care about autonomy - Michael Kuhn; Erich Gundlach (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
We consider resource allocation within an organisation and show how delegation bears on moral hazard and adverse selection when agents have a preference for autonomy. Agents may care about autonomy for reasons of job-satisfaction, status or greater reputation when performing well under autonomy. Separating allocations (overall budget and degree of delegation) are characterised depending on the preference for autonomy. As the latter increases, the degree of delegation assigned to productive and unproductive agents converges. If agents' preferences for monetary rewards are weak, the principal will not employ financial transfers. Pooling then arises under a strong preference for autonomy.
Keywords: D82; G31; 330; adverse selection; capital budgeting; delegation; intrinsic motivation; moral hazard